Intervensi Pemerintah Kabupaten Sumedang dalam Penanganan dan Penanggulangan Masalah Stunting di Kabupaten Sumedang - Allyah Nur Rahmani; Syaira Diasyifa Herlambang; Najwa Auliya Syarifah; Iyep Saefulrahman (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Stunting is a developmental disorder that occurs in children. This usually occurs when children are chronically malnourished during the child's growth period. Usually children who get symptoms of stunting will look proportional, but when children affected by stunting are next to children of the same age, children affected by stunting will look shorter or smaller. Even so, children who look short or small do not necessarily suffer from stunting. Children with stunting will experience poor growth and development, not only from their height that looks short, but the child's intelligence will also weaken, there will be interference when speaking, and it will be difficult when the child learns later; besides that, their immunity is classified as lower, which will be easily exposed to viruses and bacteria. The purpose of this study is to understand how the intervention of the Sumedang Regency government, especially the Health Office, Social Service, and DPPKBP3A of Sumedang Regency, contributes to handling and overcoming stunting cases in Sumedang Regency. The method used in this research is a descriptive qualitative method and literature study. The results of the research obtained are various information about the prevention and handling of stunting carried out by various related fields, both in the Health Office, Social Service, and DPPKBP3A, then the efforts and challenges faced by the agencies, and the most important thing is the source of funds in the framework of handling and overcoming stunting in Sumedang Regency. So it can be concluded that these agencies have an important role to deal with the problem of stunting and reduce the stunting rate in the Sumedang district in various ways.